Определение параметров основного колебательного состояния молекулы C2D4; Известия вузов. Физика; Т. 59, № 3 - Фомченко А. Л. Анна Леонидовна; Чжан Фанцэ; Громова О. В. Ольга Васильевна; Буттерсак Т. Торвальд (2016, 2016)
Заглавие с экрана